Andreas J. Köstenberger – Benjamin L. Merkle – Robert L. Plummer, Going Deeper with New Testament Greek. An Intermediate Study of the Grammar and Syntax of the New Testament (Nashville, Tennessee: B&H Academic 2016) - Piwowar, Andrzej (The Biblical Annals, 2018)
Book review: Andreas J. Köstenberger – Benjamin L. Merkle – Robert L. Plummer, Going Deeper with New Testament Greek. An Intermediate Study of the Grammar and Syntax of the New Testament (Nashville, Tennessee: B&H Academic 2016). Pp. 550. 49.99. ISBN 978-1-43367908-7 DOI: https://doi.org/10.31743/ba.2018.8.2.07